The ground doesn’t lie either - Braga, Márcia (Farol, 2025)
This article addresses the relationship between image and violence, focusing on a specific moment and place associated with trauma and pain. The discussion, which takes as its starting point the image of the implosion of one of the buildings in the Carandiru Complex, refers to the doctoral thesis *A Provisional Poetics and the Aesthetics of Other Emergencies: Collective Tactics to (Dis)inhabit a Women’s Prison* and the participatory installation *Neither Does the Ground Lie* (2022-present), created from collaborative processes between the Balcão da Cidadania collective and a group of women deprived of liberty at the Madre Pelletier State Women’s Prison (Porto Alegre, RS/Brazil). The theme is approached from the perspective of authors such as Susan Sontag, Suely Rolnik, Sharon Macdonald, Georges Didi-Huberman, Flávio Agostini, and William Logan & Keir Reeves. The writing still retains graphic elements present in the thesis.